Soft-Selling Pariwisata dalam Film 'Sore: Istri dari Masa Depan' (Studi Kasus Representasi Destinasi Wisata dan Strategi Promosi) - Anindita Lintangdesi Afriani; Garcia Krisnando Nathanael; Ayu Wardani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Film is a means of tourism promotion with soft-selling techniques that display physical space and form an emotional connection between characters and locations. This study aims to analyze the representation of tourist locations in the film Sore: Istri dari Masa Depan through Roland Barthes's semiotic approach, focusing on denotation, connotation, myth, and tourism soft-selling strategies depicted through cinematography. This research method uses a qualitative approach with Barthes's semiotic analysis technique, focusing on seven tourist destinations, including the city center of Grožnjan, the village of Završje, Tkalčićeva Street, Zagreb Cathedral, Zagreb City Museum, the Arctic Circle, and ARTOTEL Thamrin Jakarta. The results of this study show that the locations in the film are interpreted symbolically to strengthen the narrative of love, self-discovery, and contemplation of life. Each place is constructed through a myth that touches the audience's emotions and encourages imaginative involvement in the tourist destination. The soft-selling strategy used by the film can build tourism appeal through a narrative atmosphere and visual aesthetics that blend with the emotions of the film's main characters.